Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s40544-019-0296-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydraulic oil and lubricant additives on dynamic friction properties under various reciprocating sliding conditions

Abstract: The friction characteristics of a shock absorber are very complex because the reciprocating motion is not always identical. In this study, a device was developed and used to analyze the dynamic friction characteristics under various reciprocating sliding conditions to determine the sliding materials and hydraulic oils that improve the shock absorber performance. This study describes the influence of hydraulic oil additive on the fine reciprocating friction characteristics of steel and copper alloy. Hydraulic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After a lower friction level for amplitudes up to 2.5 mm, a relatively constant friction level between 2.5 and 10 mm occurs, followed by a recess between 20 and 30 mm. According to the studies of (Kato and Sasaki, 2019) on various lubricant additives, it was possible to achieve lower friction levels in the amplitude range of 0.1–1 mm on a tribo-tester, depending on the actual lubricant composition. Although the lubricant properties used for the present shock absorber are unknown, the occurred phenomenon might be of similar nature.…”
Section: Suspension Friction Measurementsmentioning
confidence: 99%
“…After a lower friction level for amplitudes up to 2.5 mm, a relatively constant friction level between 2.5 and 10 mm occurs, followed by a recess between 20 and 30 mm. According to the studies of (Kato and Sasaki, 2019) on various lubricant additives, it was possible to achieve lower friction levels in the amplitude range of 0.1–1 mm on a tribo-tester, depending on the actual lubricant composition. Although the lubricant properties used for the present shock absorber are unknown, the occurred phenomenon might be of similar nature.…”
Section: Suspension Friction Measurementsmentioning
confidence: 99%
“…Among them, the friction-reducing and anti-wear additives play an indispensable role in alleviating the friction and wear of the contact area by forming a physical adsorption/deposition film and/or tribochemical reaction film on the rubbing surfaces [28][29][30][31][32][33][34]. The traditional friction-reducing and anti-wear additives are usually composed of organic polar materials, such as organic molybdenum compounds [35][36][37], polymers [38], alcohols [39], esters [40][41][42], amine compounds [43], organic salts [44], ionic liquids, and their derivatives [45][46][47][48][49][50]. The strong polarity allows them to form neat adsorption films on the metallic rubbing surfaces to reduce the friction and wear of friction pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature indicated that there are two main approaches on how to evaluate the tribological behavior of hydraulic cylinders. The first one is by mathematical simulation/modeling [16][17][18][19][20], whereas the second one is by developing new lab-scale test procedures [21][22][23][24]. Currently, both approaches have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Lab-scale tests are more applicable for material development, as long as they correlate well with the component behavior. Unfortunately, until now lab-scale tribological tests [21][22][23] focus only on the frictional aspect, which determines the performance of hydraulic cylinders, but not on the wear which dictates the lifetime of this component. Moreover, the lab-scale tests that do measure wear [24] use simplified contacts and different contact geometries that do not closely resemble the actual contact.…”
Section: Introductionmentioning
confidence: 99%